2016
DOI: 10.1038/nphoton.2016.79
|View full text |Cite
|
Sign up to set email alerts
|

Polarization control in an X-ray free-electron laser

Abstract: X-ray Free-Electron Lasers (XFELs) are unique sources of high brightness coherent radiation. However, existing XFELs supply only linearly polarized light, precluding studies of chiral dynamics. A device called the Delta undulator has been installed at the Linac Coherent Light Source (LCLS) to provide tunable polarization. With a reverse tapered planar undulator line to pre-microbunch the beam and the novel technique of beam diverting, hundreds of microjoules of circularly polarized X-ray pulses are produced at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
101
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 135 publications
(101 citation statements)
references
References 36 publications
(42 reference statements)
0
101
0
Order By: Relevance
“…As the next step, we plan to extend it towards exploration of transient chirality accompanying fragmentation dynamics by inner-shell pump -inner-shell probe experiments at Xray free-electron lasers [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…As the next step, we plan to extend it towards exploration of transient chirality accompanying fragmentation dynamics by inner-shell pump -inner-shell probe experiments at Xray free-electron lasers [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in the Introduction, setups employing a number of eTOFs at various angles enables measurements of the polarization Allaria et al, 2014;Lutman et al, 2016). Moreover, temporal information such as the FEL pulse duration and arrival time can be determined with techniques involving streaking of photoelectrons by an external THz field (Grguraš et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…There, it serves as a general diagnostic tool, enabling the simultaneous observation of beam properties such as polarization and photon energy as well as beam position . In analogy to the OPIS, studies using this apparatus at FEL sources have been reported recently (Allaria et al, 2014;Lutman et al, 2016). In order to test the PCA method for OPIS operation we chose a measurement at = 52 nm with argon as the target gas, hence having simple eTOF spectra which show just the Ar 3p photoemission line.…”
Section: Fast Data Reduction For Online Analysismentioning
confidence: 99%
“…The electron bunch traverses the dechirper on-axis and no dipole kick is introduced, thus avoiding distortion to the beam orbit in the transport system as well as in the undulator, and allowing the method to be applied in high repetition-rate XFELs. Other advanced applications utilizing such a matching-based method may include the amplification of a seed pulse in a self-seeding scheme [29], x-ray pulse duration control, seeding a helical undulator for polarization control [30] and so on. Experimental studies have been planned at the LCLS.…”
Section: Discussionmentioning
confidence: 99%